An intronic alteration of the fibroblast growth factor 10 gene causing ALSG-(aplasia of lacrimal and salivary glands) syndrome - Wagenmann Martin; Balz Vera; Scheckenbach Kathrin; Hoffmann Thomas K (BMC, 2008)
Abstract Background A combined aplasia, hypoplasia or atresia of lacrimal points and salivary glands is rarely diagnosed. Those patients suffer from epiphora, xerostomia and severe dental caries. This phenotype represents the autosomal-dominant aplasia of lacrimal and salivary glands syndrome (ALSG). Recently, aberrations of the Fibroblast Growth Factor 10 (FGF10) gene have been identified to be causative for this disorder. Methods We performed a sequence analysis of the FGF10 gene of a patient with ALSG-syndrome and his also affected brother as well as 193 controls. The FGF10 transcript was analyzed using RNA extracted from primary fibroblasts of the patient's mucosa. Results We detected a novel heterozygous sequence variation in intron 2 (c.430-1, G > A) causing the ALSG syndrome. The alteration derogates the regular splice acceptor site and leads to the use of a new splice acceptor site 127 bp upstream of exon 3. The aberration was detected in the genomic DNA derived from two affected brothers, but not in 193 control individuals. Furthermore, no diseased member of the family displayed additional abnormalities that are indicative for the clinically overlapping lacrimo-auriculo-dento-digital syndrome (LADD). Conclusion This family-based approach revealed an intronic variation of the FGF10 gene causing ALSG-syndrome. Our results expand the mutational and clinical spectrum of the ALSG syndrome.